Prediction of the height and period of sea waves in the coastal waters of Meulaboh, Aceh Province, Indonesia. Issue 1 (May 2021) - Setiawan, I; Yuni, S M; Miftahuddin, M; Ilhamsyah, Y
Abstract: This research examines the prediction of sea waves in the coastal waters of Meulaboh. The sea wave prediction are based on the 2015-2019 monsoons in the coastal waters of Meulaboh. The method used is an empirical equation that consist of wave parameters, i.e., significant wave height Hmo and peak period Tp . The sea wave prediction generate an average of the height and period of the sea waves of 0.7 m; 5 s in the Southwest direction. Based on the prediction, it shows that the sea waves in Meulaboh coastal waters are influenced by the Southwest wind that blows towards the coast from the Indian Ocean.